Utilization of a cost effective Lapindo mud catalyst derived from eruption waste for transesterification of waste oils. (15th January 2016) - Talib, N.B.; Triwahyono, S.; Jalil, A.A.; Mamat, C.R.; Salamun, N.; Fatah, N.A.A.; Sidik, S.M.; Teh, L.P.
Graphical abstract: Highlights: Lapindo mud (LM) was used as catalyst in waste cooking oil (WCO) transesterification. K2 O and CaO were identified as the active species for WCO transesterification. FTIR and ESR analyses prove activated LM have higher basicity and surface defects. Under the optimum conditions, WCO transesterification reached 96.6% FAME yield. Conversion of palm oil mill effluent (POME) in optimum conditions gave 91.69% FAME. Abstract: The most remarkable property of heterogeneous-catalyzed transesterification is its recyclability which surpass the issue by homogenous catalyst. Lapindo mud (LM), an eruption waste from Indonesia, was treated into an active catalyst for transesterification. LM is reasonably tolerant to FFA, as no visible soap layer was observed during transesterification of high acid value WCO (20.723 mgKOH/g) and POME (120.48 mgKOH/g) with FAME yield of 96.6% and 91.69%, respectively. The reaction conditions obtained for both reaction are mild and comparable to currently reported conditions except LM effectively accelerated the transesterification process of WCO. Reusability test showed that LM exhibited a stable performance with less than 10% declined in FAME after the seventh run with 95% catalyst recovery. Kinetic analysis showed that both WCO and POME transesterification fitted well with Langmuir–Hishelwood first order reaction. The activation energy for WCO and POME transesterification were 55.7 and 59.75 kJ/mol. This findings shows the possibility of LM as a catalyst in general heterogeneous reaction and particularly for transesterification to produce FAME.